Silene konuralpii (Sect. Spergulifoliae, Caryophyllaceae), a new species from eastern Anatolia - Firat, Mehmet; Yildiz, Kemal (Phytotaxa, 2016)
A new perennial species, Silene konuralpii sp. nov. (Silene sect. Spergulifoliae) is described and illustrated from eastern Anatolia. A momorphological comparison with the similar species S. stenobotrys, S. spergulifolia, and S. surculosa is given as well as the ultrastructure of the leaf, seed and pollen grain. Original drawings and photographs, distribution map, notes on ecology, and IUCN conservation status are also provided.